# [Tex/LaTex] Equations Taking too much space

equationsline-spacingspacing

I have this set of equations and they are taking too much space.

What are some suggestions to make them more compact?

$$b_s(t) = \bm{p}_s \exp \left(-t \bm{B}_s\right)\bm{B}_s \bm{e}_s',$$
where
$$\bm{B}_s = (\bm{B}_1 \oplus \bm{R}_2) - \lambda_R \bm{e}'( \bm{p}_1 \otimes \bm{r}_2),$$
\begin{displaymath}
\bm{p}_s = (1 - \rho_s)(\bm{p}_1 \otimes \bm{r}_2)\bm{K},
\end{displaymath}
\begin{displaymath}
\rho_s = \lambda_R ( \bm{p}_1 \otimes \bm{r}_2) (\bm{B}_1 \oplus
\bm{R}_2)^{-1} \bm{e}_s',
\end{displaymath}
\begin{displaymath}
\bm{K}_s = (\bm{I} - \bm{U}_s)^{-1},\ \ \ \bm{U}_s = \bm{A}_s^{-1},
\end{displaymath}
\begin{displaymath}
\bm{A}_s = \bm{I} + \frac{1}{\lambda_R}( \bm{B}_1 \oplus \bm{R}_2) -
\bm{e}' ( \bm{p}_1 \otimes \bm{r}_2 ),
\end{displaymath}
\begin{displaymath}
\bm{R}_2 = \bm{B}_2 - \lambda_A\bm{Q}_2,
\end{displaymath}
\begin{displaymath}
\bm{r}_2 = (1 - \rho_2)\lambda_A \bm{p}_2\bm{K}_2,\
\end{displaymath}
\begin{displaymath}
\rho_2 = \lambda_A \bm{p}_2 \bm{V}_2 \bm{e}_2,
\end{displaymath}
\begin{displaymath}
\bm{K}_2 = (\bm{I} - \bm{U}_2)^{-1},\ \ \ \bm{U}_2 = \bm{A}_2^{-1},
\end{displaymath}
\begin{displaymath}
\bm{A}_2 = \bm{I} + \frac{1}{\lambda_A}\bm{B}_2 -  \bm{e}_2' \bm{p}_2.
\end{displaymath}


UDPATE:

Ok. So I used the "gather" command and it looks better. But there are still spaces. See below…

The equation (and displaymath) environment leaves some space above and below by default. Since you have used many of them consecutively, they add up. You should use the align environment to avoid excessive spacing you are getting.

Next time, please post a fully compilable code so that it helps others.

\documentclass[11pt]{article}
%
\usepackage{mathtools}
\usepackage{esvect}
\usepackage{amssymb}
\usepackage{bm}

\begin{document}

\begin{align}
b_s(t) &= \bm{p}_s \exp \left(-t \bm{B}_s\right)\bm{B}_s \bm{e}_s', \\
\shortintertext{where}
\bm{B}_s &=  (\bm{B}_1 \oplus \bm{R}_2) - \lambda_R \bm{e}'( \bm{p}_1
\otimes \bm{r}_2), \\
\bm{p}_s &= (1 - \rho_s)(\bm{p}_1 \otimes \bm{r}_2)\bm{K}, \notag \\
\rho_s &= \lambda_R ( \bm{p}_1 \otimes \bm{r}_2) (\bm{B}_1 \oplus
\bm{R}_2)^{-1} \bm{e}_s', \notag \\
\bm{K}_s &= (\bm{I} - \bm{U}_s)^{-1},\ \ \ \bm{U}_s = \bm{A}_s^{-1},
\notag \\
\bm{A}_s &= \bm{I} + \frac{1}{\lambda_R}( \bm{B}_1 \oplus \bm{R}_2) -
\bm{e}' ( \bm{p}_1 \otimes \bm{r}_2 ), \notag \\
\bm{R}_2 &= \bm{B}_2 - \lambda_A\bm{Q}_2, \notag \\
\bm{r}_2 &= (1 - \rho_2)\lambda_A \bm{p}_2\bm{K}_2,\  \notag \\
\rho_2 &= \lambda_A \bm{p}_2 \bm{V}_2 \bm{e}_2, \notag \\
\bm{K}_2 &= (\bm{I} - \bm{U}_2)^{-1},\ \ \ \bm{U}_2 = \bm{A}_2^{-1},
\notag \\
\bm{A}_2 &= \bm{I} + \frac{1}{\lambda_A}\bm{B}_2 -  \bm{e}_2'
\bm{p}_2.\notag
\end{align}

\end{document}


The output: